Analytic process and dreaming about analysis - Sirois, François (International journal of psychoanalysis, 2016)
Dreams about the analytic session feature a manifest content in which the analytic setting is subject to distortion while the analyst appears undisguised. Such dreams are a consistent yet infrequent occurrence in most analyses. Their specificity consists in never reproducing the material conditions of the analysis as such. This paper puts forward the following hypothesis: dreams about the session relate to some aspects of the analyst's activity. In this sense, such dreams are indicative of the transference neurosis, prefiguring transference resistances to the analytic elaboration of key conflicts. The parts taken by the patient and by the analyst are discussed in terms of their ability to signal a deepening of the analysis.